2002
DOI: 10.1007/s00056-002-0029-1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Dental and Skeletal Maturity

Abstract: The relationship between dental maturity and skeletal maturity is not sufficient for dental maturity to be used as a substitute for skeletal maturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…A Gulati (1990) 11 (r = 0.9594), Prabhakar AR, Panda AK, and Raju OS (2002) 18 (r = 0.89), Krogman W (2002) 19 (r = 0.310.69) showed high correlations between skeletal and dental maturity. On the contrary, Sahin-Saglam and Gazilerli (2002) 10 reported low correlation of dental and skeletal maturation. However, Lewis and Garn (1959) 20 (r = 0.30), Krogman W (1968) 19 (r = 0.46) and Demirjian A (1985) 8 (r = 0.17) have also reported low correlation between dental and skeletal ages.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A Gulati (1990) 11 (r = 0.9594), Prabhakar AR, Panda AK, and Raju OS (2002) 18 (r = 0.89), Krogman W (2002) 19 (r = 0.310.69) showed high correlations between skeletal and dental maturity. On the contrary, Sahin-Saglam and Gazilerli (2002) 10 reported low correlation of dental and skeletal maturation. However, Lewis and Garn (1959) 20 (r = 0.30), Krogman W (1968) 19 (r = 0.46) and Demirjian A (1985) 8 (r = 0.17) have also reported low correlation between dental and skeletal ages.…”
Section: Discussionmentioning
confidence: 95%
“… 7 The relationship between skeletal and physical maturation is well-documented, whereas contradictory views exist concerning their respective relationships with dental age. 8 - 10 …”
Section: Discussionmentioning
confidence: 99%
“…The recent study found a strong correlation between the dental and skeletal maturity stages which is in agreement with previous studies [ 14 , 20 , 27 33 ]. In contrast, Sahin [ 34 ] found an insufficient correlation between dental and skeletal maturity (0.47-0.55 in males and 0.58-0.64 in females). The reason for the difference between our findings and Sahin's findings [ 34 ] might be because they have included maxillary teeth in their study and these teeth roots overlap with neighboring structures, thus decreasing the validity of their method.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies differentiated between males and females when evaluating the correlation between skeletal maturation and dental calcification stages [ 14 , 28 , 34 ]. Therefore, we studied these correlations separately for males and females.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Mehta 14 and Felemban et al 15 , also reported there was strong correlation between third molar maturation and cervical vertebra maturation. In contrast, Mittal 16 and Saglam et al 17 , have reported poor relationship between third molar maturation and skeletal maturity. Demirjian et al also reported that dental development is unrelated to the other developmental systems, such as skeletal, somatic, and sexual maturity.…”
Section: Introductionmentioning
confidence: 94%